Can firms oversee more workers with fewer managers? - Valerie Smeets (IZA World of Labor, 2017)
Managers are supervising more and more workers, and firms are getting flatter. However, not all firms have been keen on increasing the number of subordinates that their bosses manage (referred to as the “span of control” in human resource management), contending that there are limits to leveraging managerial ability. The diversity of firms' organizational structure suggests that no universal rule can be applied. Identifying the factors behind the choice of firms' internal organization is crucial and will help firms properly design their hierarchy and efficiently allocate scarce managerial resources within the organization.
Keywords: M5; M54; 330; hierarchies; span of control; assignment; learning; knowledge; human resource management practices